The Effect of Mucoadhesive Gel Containing Satureja Hortensis Extract 1% on Severity of Chemotherapy-induced Mucositis Pain in Children: A Randomized Clinical Trial - Mohammad Arshadi bostanabad (International Journal of Pediatrics, 2018)
Background: One of the symptoms of mucositis caused by chemotherapy is pain. Mucositis management is initiated by assessment of oral hygiene and management of pain. Many uses have been mentioned for Satureja hortensis in traditional medicine. The study was carried out with the aim of determining the effect of Satureja hortensis extract mucoadhesive gel of 1% on severity of mucositis-induced pain in children under chemotherapy. Materials and Methods This randomized parallel double-blind clinical trial was carried out on 60 children who were affected by mucositis following chemotherapy in 2016. The samples were randomly assigned into two groups of intervention and control. The intervention group applied Satureja hortensis extract gel of 1% and the control group applied the placebo gel twice daily for 5 days after the onset of mucositis along with routine treatment. Oral mucosa was evaluated daily. Also, the Oucher pain tools and a demographic checklist were used. The data was analyzed using SPSS version 13.0 software. Results: The obtained data showed that the two groups had statistical difference in terms of the severity of the pain relief during the time, and pain severity reduced from 3.5±2.1 to 0.0 ± 0.0  in intervention group and 3.1 ± 1.8 to 0.4 ± 1.0 in control group in fifth day (p